Agriculture for improved nutrition: Seizing the momentum - Fan, Shenggen; Yosef, Sivan; Pandya-Lorch, Rajul (International Food Policy Research Institute, 2019)
Agriculture's vast potential to improve nutrition is just beginning to be tapped. New ideas, research, and initiatives developed over the past decade have created an opportunity for reimagining and redesigning agricultural and food systems for the benefit of nutrition. To support this transformation, the book reviews the latest findings, results from on-the-ground programs and interventions, and recent policy experiences from countries around the world that are bringing the agriculture and nutrition sectors closer together. Drawing on IFPRI's own work and that of the growing agriculture-nutrition community, this book strengthens the evidence base for, and expands our vision of, how agriculture can contribute to nutrition. Chapters cover an array of issues that link agriculture and nutrition, including food value chains, nutrition-sensitive programs and policies, government policies, and private sector investments. By highlighting both achievements and setbacks, Agriculture for Improved Nutrition seeks to inspire those who want to scale up successes that can transform food systems and improve the nutrition of billions of people.